2007
DOI: 10.2527/jas.2006-653
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for growth and carcass traits of Brahman steers1,2

Abstract: Spring-born purebred Brahman bull calves (n = 467) with known pedigrees, sired by 68 bulls in 17 private herds in Louisiana, were purchased at weaning from 1996 through 2000 to study variation in growth, carcass, and tenderness traits. After purchase, calves were processed for stocker grazing on ryegrass, fed in a south Texas feedlot, and processed in a commercial facility. Carcass data were recorded 24 h postmortem. Muscle samples and primal ribs were taken to measure calpastatin activity and shear force. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
35
9
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 34 publications
20
35
9
10
Order By: Relevance
“…Hump height (HMP) was measured as a component of the MSA system, as an indicator of the B. indicus content of carcasses. The trait was more heritable in BRAH than TCOMP (h 2 = 0.21 and 0.06, respectively), though the estimate for BRAH was lower than those presented in the literature, where Smith et al (2007) and Riley et al (2003) reported heritabilities of 0.38 and 0.52, respectively.…”
Section: Genetic and Phenotypic Variances And Heritabilities For Carccontrasting
confidence: 40%
See 1 more Smart Citation
“…Hump height (HMP) was measured as a component of the MSA system, as an indicator of the B. indicus content of carcasses. The trait was more heritable in BRAH than TCOMP (h 2 = 0.21 and 0.06, respectively), though the estimate for BRAH was lower than those presented in the literature, where Smith et al (2007) and Riley et al (2003) reported heritabilities of 0.38 and 0.52, respectively.…”
Section: Genetic and Phenotypic Variances And Heritabilities For Carccontrasting
confidence: 40%
“…Table 5 presents the additive and phenotypic variances and heritabilities for carcass and meat quality traits in BRAH and TCOMP steers. Several studies (O'Connor et al 1997;Elzo et al 1998;Newman et al 2002;Johnston et al 2003b;Reverter et al 2003a;Riley et al 2003;Domingue 2005;Smith et al 2007) have examined the genetic parameters of meat quality and carcass traits in tropically adapted beef cattle. Generally, levels of phenotypic variation and heritabilities in this study were consistent with those presented by Johnston et al (2003b) and Reverter et al (2003b) from previous studies conducted by the Beef CRC in Australia.…”
Section: Genotype Differencesmentioning
confidence: 99%
“…Detailed management procedures were given by Smith et al (2007). Briefly, calves were castrated, vaccinated for appropriate diseases, dewormed, dehorned if necessary, and backgrounded through autumn until ryegrass (Lolium multiflorum) could be grazed in early winter each year.…”
Section: Methodsmentioning
confidence: 99%
“…Riley et al (2003) reported low heritability estimates (0.14 to 0.06) for shear force measurements after 7, 14 and 21 days of loin steaks from Brahman steers and heifers fed in Florida. Smith et al (2007) reported slightly higher heritability estimates (0.29 ± 0.14 and 0.20 ± 0.11, respectively) for shear force measured on loin steaks aged 7-and 14-day postmortem from Brahman steers fed and processed in south Texas. Relatively low heritability estimates and the time required to obtain shear force data to establish meaningful sire expected progeny differences for shear force suggest that other methods for determining the genetic merit for tenderness should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Kilpatrick and Steen (1999) reported that the estimates of (co)variance components will lead to the establishment of carcass correlation curves over time and the development of a predictive model. In many published articles, covariances between growth and carcass traits at specific (discrete) ages are provided (Bergen et al, 2006a,b;Smith et al, 2007), and essential information regarding the estimation of covariances between longitudinal growth data and carcass quality traits is often lacking.…”
Section: Introductionmentioning
confidence: 99%